CONTROL AND MODELING PARAMETERS FOR HEAT DIAGNOSTICS OF POWER ELECTRICAL EQUIPMENT FAILURE: Array - Yesaulov, S.; Babichevа O.; Rogozhina, K. (Municipal economy of cities. Series: «Economy science», 2019)
It has been analyzed the advantages and disadvantages of the popular methods of thermal diagnostics of electric motors used in electric vehicles and public utilities. The research results of a remote sensor-transmitter for monitoring the heating temperature of various parts of the equipment relatively the ambient temperature are presented. It has been illustrated the examples of using a temperature sensor with a modulator for converting information messages according to the principle of "temperature-frequency", which made it possible to achieve measurement accuracy with an error of ± 0.25 to ± 0.07 ° C. It has been proposed a hardware path of the selective heating assessment of traction electric motors with various classes insulation. Examples of modeling the normalized thermal regimes of direct current traction electric motor and the identification of possible failures during abnormal components heating are illustrated. Using the Matlab package tools, it has been given examples of thermal processes approximation, used to analyze stochastic thermal conditions and form a primary audio library of possible failures for training a neural network expert of traction electric motors heating. It has been considered the application of the forward propagation perceptron with one hidden layer in the synthesis of an artificial neural network expert for the heat generation problems classification in traction electric motors. It has been determined the algorithm for comparing input and output features using a frequency comparator, which modeling is performed in the Matlab environment. The training neural network expert methods using a test board with low-frequency generators and the teacher synthesis methods, reducing the time spent for experimental testing of a neural network system for thermal diagnostics of traction electric motors, which allowed with an error (SSE / MSE) of 0.01 to achieve this result with less 100 eras. In the experimental artificial neural experts (ANE), the approximation time of the initial random data and the technical state identification of the TED did not exceed 0.5 s. This ANE allows to expand the diagnosed range of problems through additional training, using control tools: levels of brush sparking and vibration; smoke from heated zones, etc., specified by the user. The proposed real-time remote diagnosis system of vehicle failures can significantly reduce costs of daily maintenance on routes and affect the vehicle service culture.